Healable epoxy‐based dielectric semi‐interpenetrating networks with different degrees of cross‐linking. Issue 18 (22nd December 2021) - Sun, Wenjie; Luo, Jiaming; Zhang, Lei; Liang, Yujie; Chen, Yue; Zhou, Han; Zheng, Yiting; Cheng, Yonghong
Abstract: This study concerns thermal stimulated healable epoxy‐based semi‐interpenetrating networks (semi‐IPNs). The crosslinking degree was adjusted using different curing agents to demonstrate its influence on healability. In addition to tensile properties, this study focuses on the influence of healing efficiency on dielectric performance, especially leakage current, following mechanical damage. We propose that there exists an inverse relationship between the degree of crosslinking degree and healing. A maximum healing efficiency of 93% is obtained calculated from volume resistivity change. We find that the variable T g of the semi‐IPN crosslinking network based on epoxy resin, rather than the variable T m of the thermoplastic, determines the temperature boundary for healing. We further suggest that the healing efficiency could be influenced simultaneously by the network structure and the quantity of poly(ε‐caprolactone). These results suggest that semi‐IPNs can be used to develop healable insulating materials for electrical applications. Abstract :